TEACHING THE SUBJECTS OF "INFORMATICS AND INFORMATION TECHNOLOGY" ON THE BASIS OF MULTIMEDIA (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article discusses the methodology of solving problems related to the subject of "Informatics and Information Technologies" based on multimedia. In the teaching of this topic, it is intended to use multimedia tools to organize the lesson process and to show the process of explanation with the help of animation.